Pengaruh Leverage dan Kebijakan Dividen terhadap Investasi Perusahaan - Ida Ayu Surasmi; Ida Bagus Udayana Putra; G. Oka Warmana (Universitas Warmadewa, 2021)
In an imperfect capital market, funding decisions and dividend policy affect investment decisions. Sources of funds have different costs, so the cost of these funds will affect the analysis of investment feasibility. Agency costs both from debt and dividends can limit the company's investment. This study contributes to explaining how leverage and dividend policy influence investment decisions in companies in Indonesia. This study uses panel data regression. This study finds that the effect of dividends is stronger in limiting the company's investment. A high dividend payout reduces the company's investment the following year, whereas. leverage has no effect on the company's investment. Another finding is that investment opportunities have a positive effect on company investment, while company size has no effect on investment.